THE RELATIONSHIP BETWEEN AGE AND PARITY WITH THE INCIDENCE OF ANAEMIA AMONG PREGNANT WOMEN AT PUSKESMAS SLAWI TEGAL DISTRICT - Esti Anggraeni, Ika; Agustina, Tri (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
The maternal mortality rate (MMR) in Indonesia remains high at 305 per 100,000 live births, falling short of the target of 183 per 100,000 live births set for 2024. Puskesmas Slawi, a health center in the Tegal Regency, reported two maternal deaths in 2024 due to eclampsia and bleeding. Preliminary studies conducted at Puskesmas Slawi from June to July 2023 revealed that out of 34 pregnant women, 73.5% were anemic, 20.5% were of advanced maternal age, and 52.9% had more than two pregnancies. This study employed a correlational design and was conducted at Puskesmas Slawi in Tegal Regency from June to July 2024. The sample comprised 34 mothers in labor, utilizing secondary data for analysis. The data were processed using SPSS software and analyzed with the Chi-square statistical test. The chi-square analysis yielded a p-value of 0.687 for age, indicating no significant relationship between age and the incidence of anemia at Puskesmas Slawi, Tegal Regency. Conversely, the analysis revealed a p-value of 0.031 for parity, suggesting a significant association between parity and the incidence of anemia in the same setting. Age does not have a significant association with the incidence of anemia among pregnant women at Puskesmas Slawi, Tegal Regency; however, parity is significantly related to the occurrence of anemia in this population.